SLP Optimization-Based Voltage Profile Improvement in Unbalanced Distribution Networks With SOP Devices - CEYLAN, OĞUZHAN (My University, 2023)
The deployment of renewable energy resources (RER) such as photovoltaic (PV) and wind turbine (WT) systems has significantly improved the operation of active distribution networks (ADN). This can be seen in the technical, economic, and also environmental benefits observed over the past decade. However, since these resources have intermittent nature, they usually cause voltage and frequency fluctuations, which leads to increased system losses and instability. In this paper, sequential linear programming (SLP) is used to improve the voltage profile of unbalanced distribution networks. The method is applied to a modified IEEE-34 node test feeder. Three PV systems are installed in the system, and two of them are connected through a soft open point (SOP). The method optimizes the reactive power flow through the SOP and the third PV coming from the smart inverter, as well as the taps of the voltage regulators to reduce the voltage deviation from the reference voltage value. The voltages in the base and optimum cases are compared for each time simulation with and without the use of SOP. The results show that a more improved voltage profile is obtained after the use of SOP.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Bilgisayar Bilimleri; Algoritmalar; Matematik; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Information Systems, Communication and Control Engineering; Signal Processing; Computer Sciences; algorithms; Mathematics; Computer Science; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Bilgisayar Bilimi; Mühendislik; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; ENERJİ VE YAKITLAR; MATEMATİK, UYGULAMALI; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); COMPUTER SCIENCE; ENGINEERING; MATHEMATICS; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; ENGINEERING, ELECTRICAL & ELECTRONIC; ENERGY & FUELS; MATHEMATICS, APPLIED; Yapay Zeka; Fizik Bilimleri; Enerji Mühendisliği ve Güç Teknolojisi; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Elektrik ve Elektronik Mühendisliği; Modelleme ve Simülasyon; Artificial Intelligence; Physical Sciences; Energy Engineering and Power Technology; Renewable Energy, Sustainability and the Environment; Electrical and Electronic Engineering; Modeling and Simulation; active distribution networks; photovoltaic Systems; Renewable energy resources; soft open point